The geographical distribution of the mammalia - Halstead, Oscar Hugo (My University, 1895)
Introduction: The study of animal life, of the present, though more especially of the past forms, aside from the interest and information which may be gained from a geological point of view, is a very important one. It is by this study that we are enabled to form theories as to when and where they originated, and how they developed and finally where distributed in such a peculiar manner all over the earth’s surface. This latter, the study of animal distribution, gives a good basis for the formation of theories as regards the original land surface of the earth and the various change which it has undergone through the different geological periods.
Citation: Halstead, Oscar Hugo. The geographical distribution of the mammalia. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Animal life; Earth; Animal distribution; Theses; Manuscripts (documents)